2018
DOI: 10.2174/1874609810666170707101548
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of ERCC2/XPD and ERCC6/CSB Wild Type Alleles in Protection Against Aging and Cancer

Abstract: Homozygous wild type alleles encoding XPD and CSB proteins with optimal properties were shown to affect human lifespan, risk of developing bladder cancer, its progression and recurrence under certain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…It should be investigated in the future at which extent this defect, if confirmed in all CS patients, is correlated with and participates to the severity of the disease, whether CSA is implicated in the same pathway as CSB, and also whether it is operating in UVSS patients that lack the progeroid phenotype and whose cells do not display the HTRA3/POLG1/mitochondrial defect 22 . Finally, these data provide a DNA repair-independent mechanistic explanation for the reported association between high CSB levels and tumor proliferation 55 , and CSB polymorphism association with longevity 62 , supporting a key regulatory role of CSB in the ageing/cancer axis.…”
Section: Discussionmentioning
confidence: 51%
“…It should be investigated in the future at which extent this defect, if confirmed in all CS patients, is correlated with and participates to the severity of the disease, whether CSA is implicated in the same pathway as CSB, and also whether it is operating in UVSS patients that lack the progeroid phenotype and whose cells do not display the HTRA3/POLG1/mitochondrial defect 22 . Finally, these data provide a DNA repair-independent mechanistic explanation for the reported association between high CSB levels and tumor proliferation 55 , and CSB polymorphism association with longevity 62 , supporting a key regulatory role of CSB in the ageing/cancer axis.…”
Section: Discussionmentioning
confidence: 51%
“…For example, the MSH2 65 and MSH6 66 played roles in mismatch repair; The RAD51 65 played a role in homologous recombination; The SMC5 67 and DNA ligase (LIG1) 68 were with a role in chromosome structural maintenance; CHD1 69 and CHD4 70 were the critical chromatin remodelers. Some genes previously reported to be associated with genome instability, including the DNA endonuclease ERCC2 71,72 and ERCC6 73 , the cohesion protein NIPBL 72,74,75 , the DNA repair protein TRIP11 76 , and the chromatin remodeling factor SMARCA2 77 , were also recaptured by our method. We also observed that mutator genes were enriched in calcium ion transport (GO:0006816), glycerophospholipid biosynthesis progress (GO:0046474), and regulators of kinase activity (GO:0043549).…”
Section: Mutagene Recaptured Known and Identified New Mutator Genesmentioning
confidence: 97%
“…Single nucleotide polymorphisms have been identified in several exons of the ERCC6 gene, such as rs2228528, rs228526, and rs2228529. The mutant of ERCC6 gene has been largely investigated in a variety of cancers [7][8][9], but the effect of ERCC polymorphism in different genetic loci and cancers is not same.…”
Section: Introductionmentioning
confidence: 99%
“…This mutation in the ERCC6 rs2228526 may diminish its activity, further resulting in a defect in overall NER pathway. Recent studies have reported the association between ERCC6 rs2228526 polymorphism and risks of various cancers [7,[10][11][12][13][14][15][16][17][18][19][20][21][22]. However, the results of these studies remained controversial.…”
Section: Introductionmentioning
confidence: 99%